False Friends in Teaching Polish to Ukrainians - Banach, Agnieszka (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
The aim of this article was to collect, present and describe pairs of lexemes from Polish and Ukrainian languages that sound identical/very similar, but differ in meaning - the so-called false friends - and to indicate ways, both for teachers and learners, to avoid the resulting problems while learning Polish as a foreign language. The material was collected during a year of work with Ukrainian refugees who attended a language course at the Centrum Służby Rodzinie in Łódź. The analysis carried out shows that despite many similarities between the languages discussed, there are many differences and linguistic traps that may significantly impede the process of learning Polish as a foreign language for Ukrainians.